Examinations of DRD4, DRD5 and SNAP-25 as candidate genes in Attention Deficit Hyperactivity Disorder - Lowe, Naomi Temple (Trinity College (Dublin, Ireland). Department of Genetics, 2005)
Attention deficit hyperactivity disorder (ADHD) is a common early onset childhood disorder. Symptoms o f the disorder include inattentiveness, impulsiveness, distractibility and hyperactivity. Family, twin and adoption studies have estimated the heritability of ADHD to be 70-90% and it is believed that this genetic contribution to the disorder takes the form of multiple susceptibility genes of small individual effect. The dopaminergic neurotransmitter system has been implicated in the aetiology of ADHD by animal, pharmacological, neuroimaging and molecular studies and a number of susceptibility genes for the disorder have been identified. The aim of this thesis was to explore the molecular genetics of ADHD in relation to three dopaminergic related genes (DRD4, DRD5 and SNAP-25) using a sample of DSM IV diagnosed ADHD probands and their parents.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin